2009
DOI: 10.15283/ijsc.2009.2.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fetal Tissue-derived Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) have unique immunologic properties that may someday prove useful in cell-based therapy for various degenerative diseases. Its potential is limited, however, by several factors, including the rarity of these cells and difficulty in isolating them. To evaluate their potential as new sources for cell therapy, we isolated MSCs from human fetal tissue (hfMSC) derived from spontaneous abortus (8∼10 weeks) then studied their cell cycle and cell surface marker expression using a fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Unlike adult MSCs (i.e., BM‐MSCs), perinatal MSCs do not display major histocompatibility complex class II antigens (Anastasiu et al, ; Fariha, Chua, Tan, Tan, & Hayati, ; J. Kim, Jo, Kim, & Hwang, ; S. Liu, Yuan, et al, ; Maleki, Ghanbarvand, Reza Behvarz, Ejtemaei, & Ghadirkhomi, ; K.‐S. Shin et al, ; Tancharoen et al, ), making them more suitable for cell therapy.…”
Section: Perinatal and Fetal Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike adult MSCs (i.e., BM‐MSCs), perinatal MSCs do not display major histocompatibility complex class II antigens (Anastasiu et al, ; Fariha, Chua, Tan, Tan, & Hayati, ; J. Kim, Jo, Kim, & Hwang, ; S. Liu, Yuan, et al, ; Maleki, Ghanbarvand, Reza Behvarz, Ejtemaei, & Ghadirkhomi, ; K.‐S. Shin et al, ; Tancharoen et al, ), making them more suitable for cell therapy.…”
Section: Perinatal and Fetal Mscsmentioning
confidence: 99%
“…Even the MSCs isolated from UC and FT have been reported to vary in their differentiation into various lineages (Beeravolu et al, ; Beeravolu et al, ; Brady et al, ; Guillot, Gotherstrom, Chan, Kurata, & Fisk, ; K.‐S. Shin et al, ). Controversy regarding the differentiation potential of MSCs may be due to the variation in the niche and unreliable in vitro techniques used to differentiate and characterize MSCs.…”
Section: Potential Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to BMMSCs or AD-MSCs, fetal tissue was found to contain a sufficient number of stem cells and progenitor cells for the development and a faster rate of proliferation (Deuse et al 2011;Ishii and Eto 2014). Moreover, FA-MSCs exhibit rare chromosomal changes, a stable karyotype, late senescence, and incapacity to generate teratomas that suggest their genetic stability (Shin et al 2009). In addition, these cells are poorly antigenic, expressing HLA-G for immune tolerance during pregnancy and thus are less likely to be rejected by transplant receivers (Hunt et al 2005).…”
Section: Fetal Annexes-derived Mscsmentioning
confidence: 99%
“…Results of flow cytometry revealed that cells isolated from human umbilical cord, amniotic fluid, and placenta expressed CD13, CD29, CD44, CD73, CD90, CD105, and HLA-ABC, but not hematopoietic or endothelial specific antigens CD14, CD31, CD34, CD38, CD45, CD106, CD133, and HLA-DR (De Coppi et al 2007;Shin et al 2009;Christodoulou et al 2013) (Table 1). It is commonly accepted that potency of isolated FA-MSCs is related to the content of secretome, which includes G-CSF, TGF-β, VEGF, IGF1, BDNF, and GDNF.…”
Section: Fetal Annexes-derived Mscsmentioning
confidence: 99%